Space Science Education in Malaysia: A review based on performance improvement framework in complex systems - Zainuddin, Mohd Zambri; Mohamad, Nor Sakinah; Asillam, Mhd Fairos; Mastor, Mohd Zamri Shah; Hashim, Mohd Helmy; Radzi, Zahira Mohd (Akademi Sains Malaysia, 2019)
This paper focused on reviewing space science education in Malaysia based on the performance improvement framework in complex systems. Therefore, not all articles were reviewed but only randomly selected ones to find the pattern by analyzing activities commenced and compared to the performance improvement framework in complex systems. The data were then analyzed by using the continuous comparison method. The findings from this study implied that to improve space science education for the younger generation, it was important to view the direction of education and to understand in depth the complex systems of education as a whole. The direction of the younger generation's education system should enable them to solve complex problems efficiently. Space science education could be set as an example of how to move forward in this direction. This is due to the nature of space science education itself which is multidisciplinary. Transdisciplinary methods could be used in space science education and might act as a case of an integrated STEM model for the Malaysian Education System. Other implications of the transdisciplinary method implementation are exposure to systems thinking among scientists, teachers, educators, administrators, authorities, students and the public. The changes will take effect only if more people are aware of the importance of systems thinking as the basis in life so as to be able to understand that all the elements are interconnected in the complex systems as a whole.